2016
DOI: 10.1021/acsami.5b11022
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Facile One-Pot Solvothermal Synthesis of PEDOT–PSS/Ni–Mn–Co–O Hybrid as an Advanced Supercapacitor Electrode Material

Abstract: In this work, a novel and facile one-pot method has been developed for the synthesis of a hybrid consisting of Ni-Mn-Co ternary oxide and poly(3,4-ethylenedioxythiophene)-polystyrenesulfonate (PEDOT-PSS/NMCO) with a hierarchical three-dimensional net structure via a solvothermal-coprecipitation coupled with oxidative polymerization route. Apart from the achievement of polymerization, coprecipitation, and solvothermal in one pot, the hydroxyl (OH(-)) ions generated from the oxidative polymerization of organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…In comparison with their corresponding single oxides, Mn-based spinel oxides such as MnCo 2 O 4 and MnFe 2 O 4 would be more attractive to be explored because of the synergistic effect on redox reaction contributed by the cobalt/iron and manganese ions. 57,58 In addition, these binary metal oxides have been widely investigated as an anode for Li-ion batteries [59][60][61][62] because of their better electrical conductivity and superior electrochemical activity, in comparison with mono-metals, as well as high theoretical capacity. Nonetheless, these materials are rarely reported for anode materials in Na-ion batteries.…”
Section: Mn-based Spinel Oxidesmentioning
confidence: 99%
“…In comparison with their corresponding single oxides, Mn-based spinel oxides such as MnCo 2 O 4 and MnFe 2 O 4 would be more attractive to be explored because of the synergistic effect on redox reaction contributed by the cobalt/iron and manganese ions. 57,58 In addition, these binary metal oxides have been widely investigated as an anode for Li-ion batteries [59][60][61][62] because of their better electrical conductivity and superior electrochemical activity, in comparison with mono-metals, as well as high theoretical capacity. Nonetheless, these materials are rarely reported for anode materials in Na-ion batteries.…”
Section: Mn-based Spinel Oxidesmentioning
confidence: 99%
“…In the search for advanced sustainable energy sources, the urgent development of long-term high-efficient high energy-power resources is required. Electrochemical energy storage (EES) systems such as batteries and supercapacitors are promising for reaching the required demands due to their fast charge–discharge rates, high power ability, long cycle life for supercapacitors and high-rate capability and high energy density for batteries [ 5 , 6 ]. Among different types of rechargeable batteries, lithium-ion (Li-ion) batteries have been considered as one of the most promising EES sources on the market since 1991.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished by the use of a conducting polymer coating. The usual approach involves the application of composites of conducting polymers, such as poly­(aniline) (PANI), poly­(pyrrole) (PPy), poly­(3,4-ethylenedioxythiophene) (PEDOT), etc., with transition metal oxides as electroactive electrodes in supercapacitors to achieve performance enhancement in terms of storage and cycle life owing to the increased electrical conductivity, the additional redox activity offered by the polymer, and its chemical robustness. This is evident from the increased storage response obtained in a previous study with a composite of PEDOT:PSS (poly-(4-styrene sulfonate)), with the ternary oxide of Ni–Mn–Co attributed to the larger reaction surface area, faster ion and electron transfer ability, and good structural stability . Yet another report showed that by doping Mn ions into a Ni–Co-layered double hydroxide nanosheet-coated PANI-derived carbon structure, the energy storage performance is considerably improved for the corresponding asymmetric supercapacitor .…”
Section: Introductionmentioning
confidence: 99%